Fever of Unknown Origin: The Internist´s Challenge: Síndrome Febril Indeterminada: O Repto do Internista - Barbosa, Mário (Gazeta Médica, 2018)
Fever of unknown origin represents since the dawn of Medicine a diagnostic challenge. The authors report the case of a middle-aged man, apparently healthy, that practiced outdoor activities, admitted to our ward due to a febrile syndrome, without a categorical source, which lasted more than three weeks until conclusive diagnosis. We emphasize the importance of liver ultrasound to clarify the etiology of fever of unknown origin in mild clinical cases, and the inclusion of amebiasis in the differential diagnosis when epidemiologically justified. Received: 09/12/2016 - Accepted: 04/12/2017